SELF CONCEPT IN RELATION TO PURCHASING DECISIONS OF THRIFT FASHION PRODUCTS AMONG UNIVERSITY STUDENTS IN PONTIANAK - Abang Rahmat Hidayat; Rizki Fitlya; Risna Hayati (Jurnal EMPATI, 2025)
The increasing prevalence of thrift fashion among university student in Pontianak is driven not only by economic considerations, but also by individuals’ efforts to express themselves and construct their identities. This phenomenon indicates a potential correlation between self-concept and purchasing decisions related to thrift products. The present study aims to examine the influence of self-concept on the purchasing decisions of thrift fashion among univesity students. The subjects in this study were 100 university students studying in Pontianak. The data collection instruments used were the Self-Concept Scale and the Purchasin Decision Scale. The collected data were analyzed using simple linear regression analysis with the assistance of the SPSS program. The results of the study showed a significance value of 0,000 < 0,050, indicating a significant influence of self-concept on purchasing decisions, with an R value of 0,647, which indicates a moderate correlation. Furthermore, the coefficient of determination (R²) was 0,419, meaning that self-concept contributes 41.9% to purchasing decisions, while the remaining 58.1% is influenced by other factors not examined in this study.